Effects of Thiourea on the Corrosion of Low Carbon Steel in Hydrochloric Acid Solution - SuUiman, I. D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The c.orrosion rate of low carbon steel in 4M hydrochlwic acid with and without presence of thiourea has b.een studied by gravimetric ahd gasometric methods over the temperature range 303-333 K. The percentage protection of steel increases vvith the decrease of thimuea concentrations at various temperature range 303-333 K and approaching highest protection (86.82%) at 303K by using I X 1 o-4 M of thiourea. The high concentration .of thiourea ( lxlo-3 M), enl1ances. the corrosion rates and act as dcpolariser for the hydrogen evolution reaction, with H2S bei11g a product of the chemical depolarisation â€¢ stage. The ff2S is considered to be adsoJ’bed in the s-2 HS- state, forming activated sites where anodic dissolution is thereby enhanced. The result’s wetÂ·e discussed on basis of adsorption of dissociated thiourea molecules on steel .surface. The energies of activation have been calculated for the corrosiOn process of the carbon steel in acid from corrosion rates in: tbeabsenee and the presence of thiourea.